Fair electricity transfer price and unit capacity selection for microgrids - Zhang, Di; Samsatli, Nouri J.; Hawkes, Adam D.; Brett, Dan J.L.; Shah, Nilay; Papageorgiou, Lazaros G. (Energy economics, 2013)
Microgrids are defined as an area of electricity distribution network that can operate autonomously from the rest of the network. In order to achieve the best economic outcomes, the participants in a microgrid can benefit from cooperation in microgrid design and operation. In this paper, a mathematical programming formulation is presented for fair, optimised cost distribution amongst participants in a general microgrid. The proposed formulation is based on the Game-theory Nash bargaining solution approach for finding optimal multi-partner cost levels subject to given upper bounds on the equivalent annual costs. The microgrid planning problem concerning the fair electricity transfer price and unit capacity selection is first formulated as a mixed integer non-linear programming model. Then, a separable programming approach is applied to reform the resulting mixed integer non-linear programming model to a mixed integer linear programming form. The model is applied to a case study with a microgrid involving five participants. ► Work aims at fair benefits distribution amongst microgrid participants. ► An MINLP model is formulated based on Game theory Nash approach. ► Separable programming approach is applied to reform as an MILP model. ► Decision variables include electricity transfer price and unit capacity. ► Results from a five participant microgrid indicate fair benefit distribution.